Introduction to the primates - Swindler, Daris Ray (University of Washington Press, 1998)
A comprehensive guide to the evolutionary history of the world's prosimians, monkeys, and apes, and of humankind's interactions with them. This account of 65 million years of adaptation and evolution concludes with a chapter on the threat that homo sapiens now pose to the survival of the world's nonhuman primates. 42 photos. 72 drawings. A comprehensive yet compact guide to the long evolutionary history of the world's prosimians, monkeys, and apes, and the much shorter history of humankind's interactions with them, from our earliest recorded observations to the threats we now pose to their survival. Describes the major primate groups and their environments, compares the species anatomically, and considers primate behavior and its close connection with environment and evolutionary differences. Includes b & w photos and drawings. For students of primatology.